Behavior of molecules and molecular ions near a field emitter - Gault, B.; Saxey, David; Ashton, M.; Sinnott, S.; Chiaramonti, A.; Moody, M.; Schreiber, D. (Institute of Physics Publishing Ltd, 2016)
The cold emission of particles from surfaces under intense electric fields is a process which underpins a variety of applications including atom probe tomography (APT), an analytical microscopy technique with near-atomic spatial resolution. Increasingly relying on fast laser pulsing to trigger the emission, APT experiments often incorporate the detection of molecular ions emitted from the specimen, in particular from covalently or ionically bonded materials. Notably, it has been proposed that neutral molecules can also be emitted during this process. However, this remains a contentious issue. To investigate the validity of this hypothesis, a careful review of the literature is combined with the development of new methods to treat experimental APT data, the modeling of ion trajectories, and the application of density-functional theory simulations to derive molecular ion energetics. It is shown that the direct thermal emission of neutral molecules is extremely unlikely. However, neutrals can still be formed in the course of an APT experiment by dissociation of metastable molecular ions.